PENGARUH DIGITAL MARKETING, CITA RASA, DAN KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA USAHA MARTABAK ARJUNA DI ASEMBAGUS - Haris Suhud Maulana; Randika Fandiyanto; Riska Ayu Pramesthi (Fakultas Ekonomi dan Bisnis, 2026)
The increasingly competitive culinary business requires business owners to improve consumer loyalty through appropriate marketing strategies. This study aims to analyze the influence of Digital marketing, Taste, and Product quality on Consumer loyalty through consumer Satisfaction, as well as the indirect effect through consumer Satisfaction as a mediating variable. The population in this study consisted of consumer Martabak Arjuna selected based on certain criteria. The sampling technique used was nonprobability sampling with a purposive sampling method. Data analysis and hypothesis testing in this study employed the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct effect hypothesis testing using SmartPLS 3.0 indicate that Digital marketing has a positive and significant effect on consumer satisfaction, Taste has positive and significant effect on consumer satisfaction, Product quality has positive and but insignificant effect on consumer Satisfaction, Digital Marketing has negative and insignificant effect on consumer Loyalty, Taste has a significant negative effect on consumer Loyalty, Product quality has a positive and significant effect on consumer Loyalty, and consumer satisfaction has a positive and significant effect on consumer Loyalty. The result of the indirect effect hypothesis testing show that Digital marketing and Teste have a positive and significant effect on consumer Loyalty on through consumer Satisfaction, while Product quality has a positive but insignificant effect consumer Loyalty on through consumer Satisfaction.